On-the-fly thermal expansion for Monte Carlo multi-physics reactor simulations - Imron, Muhammad; Lee, Deokjung (Frontiers in Nuclear Engineering, 2024)
In this study, we present on-the-fly thermal expansion methodology for direct Monte Carlo coupled multi-physics reactor simulations. This approach allows the problem geometry to be thermally expanded on-the-fly during particle tracking using local temperatures, such as pin-averaged temperatures, obtained from the thermal-hydraulics solver. Numerical experiments demonstrated that modeling thermal expansion with local temperatures for thermal expansion improves the accuracy of reactor simulations, both for reactor eigenvalue and pin powers, compared to using global core-averaged temperatures. Additionally, the use of thermal expansion also improves the isothermal temperature coefficients, making them approximately 0.77 pcm/K closer to the measured data. Finally, results for depletion problems showed that incorporating thermal expansion in direct reactor modeling enhances the predicted critical boron concentration, particularly at high power and higher fuel burnup. These findings suggest that including thermal expansion in reactor modeling is essential for improving the fidelity of simulations.